2018 AIChE Spring Meeting & 14th Global Congress on Process Safety proceedings : perspectives on process safety from around the world (Center for Chemical Process Safety/AIChE, 2018)
Perspectives on Process Safety from Around the World is consist of sessions that strive to provide a space for different regions around the world to get together at the Global Congress and discuss the issues that are significantly impacting the development in Process Safety in their regions, considering the particular needs of language, and cultural characteristics of each one. --